Responding to The Digitalization Challenges of PT. Pos Indonesia By Increasing The Role of Compensation and Motivation in Driving Employee Performance - Candra Setiawan; Yenny Maya Dora (IJSM, 2026)
This study aims to analyze the effect of compensation on employee performance with work motivation as a mediating variable at the Head Office of PT. Pos Indonesia (Persero) in facing the challenges of the industry 4.0 era. The research approach used is quantitative with the path analysis method, supported by data processing using SPSS. The research sample consisted of 186 respondents selected using the Slovin formula from a population of 345 employees. The research instrument was a closed questionnaire using a 5-point Likert scale, and its validity and reliability were tested. The results showed that compensation significantly influenced employee motivation and performance, both directly and indirectly. Compensation had a direct effect on motivation with a coefficient of 0.857, and on performance by 0.669. Meanwhile, the indirect effect of compensation on performance through motivation was 0.342. The results of the Sobel test support that motivation is a significant mediating variable. These findings reinforce the importance of strategic and fair compensation design as a tool to encourage organizational productivity and adaptation in digital transformation. This study also reveals the need to strengthen non-financial compensation aspects and develop a work environment that supports intrinsic motivation for the sustainability of organizational performance.